2014
DOI: 10.1104/pp.114.252379
|View full text |Cite
|
Sign up to set email alerts
|

High Light-Dependent Phosphorylation of Photosystem II Inner Antenna CP29 in Monocots Is STN7 Independent and Enhances Nonphotochemical Quenching

Abstract: Phosphorylation of the photosystem II antenna protein CP29 has been reported to be induced by excess light and further enhanced by low temperature, increasing resistance to these stressing factors. Moreover, high light-induced CP29 phosphorylation was specifically found in monocots, both C3 and C4, which include the large majority of food crops. Recently, knockout collections have become available in rice (Oryza sativa), a model organism for monocots. In this work, we have used reverse genetics coupled to bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 83 publications
1
41
0
Order By: Relevance
“…Considering the similar rate of accumulation of these proteins in ML, we propose their direct and concerted involvement in turnover of PsbA, which is already enhanced at moderate irradiances (Aro et al ., ). It is well known that the functioning and repair of photosynthetic protein complexes, especially PSII, is largely regulated by reversible protein phosphorylation (Allen et al ., ; Betterle et al ., ). A roughly twofold increase in the amount of the luminal kinase NDPK3, which uses ATP to synthesize the GTP required for the degradation of PsbA (Spetea et al ., ; Spetea and Lundin, ), was already observed in ML versus LL plants and further exacerbated in HL versus ML plants (Figure ), pointing out its major role in efficiently sustaining PSII turnover even at moderate intensities.…”
Section: Resultsmentioning
confidence: 97%
“…Considering the similar rate of accumulation of these proteins in ML, we propose their direct and concerted involvement in turnover of PsbA, which is already enhanced at moderate irradiances (Aro et al ., ). It is well known that the functioning and repair of photosynthetic protein complexes, especially PSII, is largely regulated by reversible protein phosphorylation (Allen et al ., ; Betterle et al ., ). A roughly twofold increase in the amount of the luminal kinase NDPK3, which uses ATP to synthesize the GTP required for the degradation of PsbA (Spetea et al ., ; Spetea and Lundin, ), was already observed in ML versus LL plants and further exacerbated in HL versus ML plants (Figure ), pointing out its major role in efficiently sustaining PSII turnover even at moderate intensities.…”
Section: Resultsmentioning
confidence: 97%
“…In the same study, barley and maize plants showed increased CP29 phosphorylation also under high light, cold, and salt stress. The increase of CP29 phosphorylation upon exposure to high light was further observed both in dicots and monocots and associated with PSII damage (Betterle, Ballottari, Baginsky, & Bassi, 2015; Fristedt & Vener, 2011). As a result, no common pattern of PSII‐LHCII phosphorylation in drought stress can be deduced among different species.…”
Section: Discussionmentioning
confidence: 95%
“…The amino acid sequence of P. patens STN8 kinase showed a conserved C-terminal catalytic domain with other plant species, while the main differences were found in the N terminus, already shown to be variable among species, possibly related to the different substrate specificity of the kinase in different species (Betterle et al, 2015;Supplemental Fig. S5).…”
Section: Determination Of Stn8 Kinase-dependent Phosphorylation In Pmentioning
confidence: 89%
“…Although the exact physiological role of phospho-LHCB6 in P. patens has still to be elucidated, the phosphorylation of minor antenna proteins in other plant species has been mainly related to a photoprotective role, e.g. NPQ (Betterle et al, 2015) or energy spillover (Ferroni et al, 2018). This might be the case also in P. patens, where LHCB6 phosphorylation is enhanced particularly upon the HL treatment.…”
Section: P Patens Lhcbm and Lhcb6 Antenna Protein Phosphorylation Dementioning
confidence: 99%